Labor Market Effects of Economic Integration - The Impact of Re-Unification in German Border Regions - Thiess Büttner; Johannes Rincke (Center for Economic Studies and ifo Institute (CESifo), 2004)
The paper argues that economic integration causes problems for the labor market of high-wage countries due to cross-border labor mobility and the accompanying increase in labor supply. Empirical evidence is provided from an analysis of regional labor market effects of German re-unification. In the aftermath of the re-unification shock, despite some gain in employment, border regions situated on the former German-German border are found to have experienced a fall in the relative wage position and an increase in unemployment relative to other West-German regions. As this points to adverse labor supply effects for resident workers due to cross-border labor mobility, this result is bad news for EU regions situated on the border with the Accession countries in Central and Eastern Europe.
Keywords: F15; J61; R23; 330; economic integration; border regions; EU enlargement; German re-unification; differences in differences estimation